(untitled) (African Journal of Biomedical Research, 2019)
The occurrence of antibiotics resistant food borne pathogens continues to be a growing concern to the food industry. However, as eggs continue to be a source of cheap protein, there are few information on the prevalence of these antimicrobial resistant Escherichia coli O157:H7 in table eggs. Therefore, this study was designed to determine the occurrence and antibiotic sensitivity profile of Escherichia coli O157:H7 in table eggs from poultry farms in Ibadan, Oyo State Nigeria. Eggshells and contents of 360 table eggs were sampled purposively from 12 farms (2 farms per local government) in Ibadan. Enumeration for Escherichia coli O157:H7, total aerobic bacteria and coliform counts was performed using standard procedures. The antibiotics sensitivity test was carried out using the Kirby Baeur disc diffusion method. Data were analysed using descriptive statistics and ANOVA at α 0.05. The prevalence of Escherichia coli O157:H7 was 7(9.8%) which was entirely from egg shell. The Total aerobic bacteria count (Mean Log CFU) was 1.43 ±1.65 and 4.95 ± 0.24 for egg contents and shell, respectively, and the Total coliform count was 1.36±1.46 and 4.84 ± 0.33 for egg contents and shell, respectively. All isolates were resistant to Ampilillin, Ceftadizine, Cefuroxime and Amoxicillin. In all 100% was multidrug resistant. The isolates were mostly susceptible to Ciprofloxacin (87.5%). and Ofloxacin (87.5%). Improvement in the hygienic conditions of poultry farms and control of the misuse and overuse of antibiotics in poultry is therefore strongly recommended.